Analysis Of Learning Difficulties In The Microeconomic Theory Course For Students Of The Economic Education Study Program, Pamulang University - Syafaatul Hidayati (Universitas Hamzanwadi, 2025)
This study aims to examine the various learning obstacles experienced by students in the Microeconomic Theory course in the Economic Education Study Program at Pamulang University. The course requires strong analytical skills and a deep understanding of concepts, which often pose challenges for students. The research employed a qualitative descriptive approach, with data collected through observations and interviews with students. The findings indicate that learning difficulties are influenced by both internal and external factors. Internal factors include insufficient mastery of basic economic concepts, limited mathematical ability, and low levels of learning motivation. External factors involve the use of predominantly conventional teaching methods, limited utilization of learning media, and a lack of contextual examples in the learning process. Therefore, this study recommends the implementation of more interactive and contextual learning strategies to enhance students’ understanding and learning outcomes in the Microeconomic Theory course.